Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which of the given expressions is a factor of the polynomial [tex]\(3x^3 - 4x^2 - 13x - 6\)[/tex], we can utilize the Factor Theorem. The Factor Theorem states that a polynomial [tex]\(f(x)\)[/tex] has a factor [tex]\((x - k)\)[/tex] if and only if [tex]\(f(k) = 0\)[/tex].
We need to test each candidate to see if substituting the corresponding value into the polynomial yields zero. Let's denote the polynomial by [tex]\(p(x) = 3x^3 - 4x^2 - 13x - 6\)[/tex]. Now we will evaluate [tex]\(p(x)\)[/tex] for each root:
### Option A: [tex]\(x - 4\)[/tex]
To test if [tex]\(x - 4\)[/tex] is a factor, we substitute [tex]\(x = 4\)[/tex] into the polynomial:
[tex]\[ p(4) = 3(4)^3 - 4(4)^2 - 13(4) - 6 \][/tex]
[tex]\[ = 3(64) - 4(16) - 52 - 6 \][/tex]
[tex]\[ = 192 - 64 - 52 - 6 \][/tex]
[tex]\[ = 70 \][/tex]
Since [tex]\(p(4) = 70\)[/tex], [tex]\(x - 4\)[/tex] is not a factor.
### Option B: [tex]\(x + 3\)[/tex]
To test if [tex]\(x + 3\)[/tex] is a factor, we substitute [tex]\(x = -3\)[/tex] into the polynomial:
[tex]\[ p(-3) = 3(-3)^3 - 4(-3)^2 - 13(-3) - 6 \][/tex]
[tex]\[ = 3(-27) - 4(9) + 39 - 6 \][/tex]
[tex]\[ = -81 - 36 + 39 - 6 \][/tex]
[tex]\[ = -84 \][/tex]
Since [tex]\(p(-3) = -84\)[/tex], [tex]\(x + 3\)[/tex] is not a factor.
### Option C: [tex]\(x + 1\)[/tex]
To test if [tex]\(x + 1\)[/tex] is a factor, we substitute [tex]\(x = -1\)[/tex] into the polynomial:
[tex]\[ p(-1) = 3(-1)^3 - 4(-1)^2 - 13(-1) - 6 \][/tex]
[tex]\[ = 3(-1) - 4(1) + 13 - 6 \][/tex]
[tex]\[ = -3 - 4 + 13 - 6 \][/tex]
[tex]\[ = 0 \][/tex]
Since [tex]\(p(-1) = 0\)[/tex], [tex]\(x + 1\)[/tex] is a factor.
### Option D: [tex]\(x + 6\)[/tex]
To test if [tex]\(x + 6\)[/tex] is a factor, we substitute [tex]\(x = -6\)[/tex] into the polynomial:
[tex]\[ p(-6) = 3(-6)^3 - 4(-6)^2 - 13(-6) - 6 \][/tex]
[tex]\[ = 3(-216) - 4(36) + 78 - 6 \][/tex]
[tex]\[ = -648 - 144 + 78 - 6 \][/tex]
[tex]\[ = -720 \][/tex]
Since [tex]\(p(-6) = -720\)[/tex], [tex]\(x + 6\)[/tex] is not a factor.
Conclusively, the only factor is:
[tex]\[ \boxed{x + 1} \][/tex]
We need to test each candidate to see if substituting the corresponding value into the polynomial yields zero. Let's denote the polynomial by [tex]\(p(x) = 3x^3 - 4x^2 - 13x - 6\)[/tex]. Now we will evaluate [tex]\(p(x)\)[/tex] for each root:
### Option A: [tex]\(x - 4\)[/tex]
To test if [tex]\(x - 4\)[/tex] is a factor, we substitute [tex]\(x = 4\)[/tex] into the polynomial:
[tex]\[ p(4) = 3(4)^3 - 4(4)^2 - 13(4) - 6 \][/tex]
[tex]\[ = 3(64) - 4(16) - 52 - 6 \][/tex]
[tex]\[ = 192 - 64 - 52 - 6 \][/tex]
[tex]\[ = 70 \][/tex]
Since [tex]\(p(4) = 70\)[/tex], [tex]\(x - 4\)[/tex] is not a factor.
### Option B: [tex]\(x + 3\)[/tex]
To test if [tex]\(x + 3\)[/tex] is a factor, we substitute [tex]\(x = -3\)[/tex] into the polynomial:
[tex]\[ p(-3) = 3(-3)^3 - 4(-3)^2 - 13(-3) - 6 \][/tex]
[tex]\[ = 3(-27) - 4(9) + 39 - 6 \][/tex]
[tex]\[ = -81 - 36 + 39 - 6 \][/tex]
[tex]\[ = -84 \][/tex]
Since [tex]\(p(-3) = -84\)[/tex], [tex]\(x + 3\)[/tex] is not a factor.
### Option C: [tex]\(x + 1\)[/tex]
To test if [tex]\(x + 1\)[/tex] is a factor, we substitute [tex]\(x = -1\)[/tex] into the polynomial:
[tex]\[ p(-1) = 3(-1)^3 - 4(-1)^2 - 13(-1) - 6 \][/tex]
[tex]\[ = 3(-1) - 4(1) + 13 - 6 \][/tex]
[tex]\[ = -3 - 4 + 13 - 6 \][/tex]
[tex]\[ = 0 \][/tex]
Since [tex]\(p(-1) = 0\)[/tex], [tex]\(x + 1\)[/tex] is a factor.
### Option D: [tex]\(x + 6\)[/tex]
To test if [tex]\(x + 6\)[/tex] is a factor, we substitute [tex]\(x = -6\)[/tex] into the polynomial:
[tex]\[ p(-6) = 3(-6)^3 - 4(-6)^2 - 13(-6) - 6 \][/tex]
[tex]\[ = 3(-216) - 4(36) + 78 - 6 \][/tex]
[tex]\[ = -648 - 144 + 78 - 6 \][/tex]
[tex]\[ = -720 \][/tex]
Since [tex]\(p(-6) = -720\)[/tex], [tex]\(x + 6\)[/tex] is not a factor.
Conclusively, the only factor is:
[tex]\[ \boxed{x + 1} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.